Gambaran Dampak Kecemasan dan Gejala Psikologis pada Anak Korban Bencana Gempa Bumi di Lombok - Zurriyatun Thoyibah; Meidiana Dwidiyanti; Misroh Mulianingsih; Winda Nurmayani; Reza Indra Wiguna (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2019)
Introduction: Earthquakes that occur always have a psychological impact on all victims, including children. Limited studies explore anxiety and symptoms of children’s psychological problems. This study aims to describe anxiety and psychological symptoms on children caused by the earthquake in Lombok, West Nusa Tenggara.Method: This study uses a mix-method design with a sample of 47 respondents in SDN 2 Penimbung West Lombok, the sample was determined by purposive sampling technique. Quantitative data analysis using the RCMAS-2 questionnaire (Revised Children's Manifest Anxiety Scale; second edition) and qualitative analysis using the method of in-depth interview.Results: Most of the respondents of children included normal anxiety category 85.11%, while 14.89% belonged to the category of clinical anxiety. The results of the qualitative study showed that there were changes in attitudes in children, such as children becoming more sensitive, easily crying, irritable, children easily panicking and crying if they heard something thundering, children often worried about entering the house, they were initially cheerful but after earthquakes occur more children are quiet and withdraw.Conclusion: Earthquakes that occur cause symptoms of clinical anxiety in some children, which are manifested in everyday life both at home and at school. Future research is expected to provide appropriate therapy for children affected by disasters so that the psychological impact experienced can be reduced.